Wearing compression garments differently affects monopodal postural balance in high-level athletes - Baige, K.; Noé, F.; Paillard, T. (Scientific Reports, 2020)
This study investigated the acute effects of compression garments (CG) on balance control in elite athletes. 15 male professional handball players were recruited. They had to stand as motionless as possible in a monopedal stance on a force plate with the eyes closed and on a wobble board with the eyes open, while wearing CG or not. Centre of foot pressure mean velocity and surface area were calculated. Statistics were first calculated with the data from the whole sample. A hierarchical cluster analysis was also performed in order to categorize the participants` behaviours into subgroups with similar characteristics. The whole group analysis showed that there were no significant effects attributed to CG. The clustering analysis identified two distinct and homogeneous subgroups of participants. Only athletes with the best balance abilities at baseline could benefit from CG wearing to improve their balance control. These athletes, who swayed less and were more sensitive to somatosensory manipulation due to CG wearing, seem to control balance by adopting a support-dependent preferred sensorimotor tactic. Our findings suggest that amongst high-level athletes, the ability to benefit from CG wearing to improve balance control seems to depend on participants` intrinsic balance skills and/or preferred sensorimotor tactics.